Análise da concentração de resistina, PAI-1 e adiponectina e do perfil metabólico em crianças e adolescentes com excesso de peso e baixa estatura leve - Pereira, Joicy Karla Grangeiro (2021)
The coexistence of stunting associated with weight excess is called a double burden of malnutrition. In the world more than 150 million children are stunting and over 340 million children and adolescents are weight excess or obese. Changes several in dietary patterns and physical activity contributed to these changes and occurred more rapidly in developing countries. Excess fat is associated with changes in adipokines concentrations, such as leptin, resistin, PAI-1 and adiponectin. The objective was to analyze the concentrations of resistin, PAI-1, adiponectin and the metabolic profile of children and adolescents with short stature and excess weight. A nutritional assessment was carried out of 2,967 children and adolescents of both sexes 7 to 16 years from 09 public schools in the city of João Pessoa/PB. These were allocated into two groups according to the following anthropometric inclusion criteria: 1) Weight excess group (n=23), height-for-age > 0.0 and <2.0 Z score and body mass index-for- age (BMI/I) > 1.0 score Z; 2) Double burden of malnutrition group (n=22), height-for-age < - 1.0 Z score and BMI/I > 1.0 Z score. To check the nutritional status, weight, height, sex, date of birth, waist circumference (WC) and hip (CQ), waist-to-hip ratio (WHR) and waist-to-height ratio (WHR) of children and adolescents were collected. Glucose, triglycerides, total cholesterol and fractions were analyzed using the enzymatic colorimetric method and insulin and leptin using the chemiluminescence method, resistin, PAI-1 and adiponectin through of Multiplex kits. Insulin sensitivity was assessed using Homeostasis model assessment (HOMA-IR). In the anthropometric assessment, 2.26% (n = 67) were short for age and 97.74% (n = 2,900) adequate stature for age. Regarding BMI / I, 7.75% (n = 230) were underweight, 62.82% (n = 1,864) adequate weight, 16.38% (n = 486) overweight and 13.05% (n = 387) obesity. The LDL (Low Density Lipoproteins) concentration in girls of the overweight group was 70,27 + 14,97 mg / dl, significantly higher value than the double burden group 49,03 + 19,11 mg / dl, p= 0,009, while the glucose concentration was higher in the latter 4,50 + 4,27-4,83 mmol/l and 5,27 + 5,05-5,49 mmol/l, p= 0,025. The boys in the double burden group had significantly higher resistin levels compared to the overweight group 20,48 + 17,80-31,21 ng/ml e 13,54 + 8,80- 18,19 ng/ml, p= 0,027. The girls showed a positive correlation between adiponectin and WHR (0.423, p <0.05). While boys showed a negative correlation between adiponectin and insulin (0.414, p <0.05) and MLI (-0.458, p <0.05) and PAI-1 showed a positive correlation with resistin (0.437, p <0.05), WC (0.464, p <0.05) and LDL (0.446, p <0.05). The increase in the concentration of resistin in boys and glucose in girls with a double burden of malnutrition indicate that short stature associated with excess weight may show changes additional in adipokines in relation to excess weight.